Peningkatan Kreativitas Siswa Dengan Menggunakan Metode Discovery Dalam Pembelajaran Seni Tari Di Kelas XI SMA Negeri 6 Padang - Rangga Saputra; Yuliasma Yuliasma; Fuji Astuti (SENDRATASIK UNP, 2019)
This article aims to describe the increasing creativity of students by using the method of discovery in learning the art of dance in class XI SMA Negeri Padang 6. The type of research conducted in this research is the Research Action class (PTK). This research was conducted with two cycles of among others a cycle I and cycle II. The object of this study was 6 SMA Negeri Padang students i.e. class XI IPA 5 of 32 people. Types of data using primary data and secondary data.Engineering data collection done by the study of librarianship, observation, deeds and test documentation. Thoroughly data were analyzed using student percentage and use the criteria of ketuntasan individuals and groups with a Minimum of 75% thoroughly criteria. The results showed that use of the method of discovery in learning the art of dance, in particular culture can enhance creativity and learning are able to make the students directly involved in learning, let alone learning the practice of dance. Learning outcomes grade XI IPA 5 on cycle I the results of learning (psychomotor) students only achieve 59.91%. And the results of learning (cognitive) students only reached 15.62%. cycle II student learning outcomes (psychomotor) students reach 92.18% and (cognitive) 82.50%. so there has been an increase in the results of learning the art of dance by using the method of discovery and targets to be achieved has been successful.